A Phase II Clinical Trial of Pembrolizumab and Enobosarm in Patients with Androgen Receptor‐Positive Metastatic Triple‐Negative Breast Cancer. (24th November 2020) - Yuan, Yuan; Lee, Jin Sun; Yost, Susan E.; Frankel, Paul H.; Ruel, Christopher; Egelston, Colt A.; Guo, Weihua; Gillece, John D.; Folkerts, Megan; Reining, Lauren; Highlander, Sarah K.; Robinson, Kim; et al.
Abstract: Lessons Learned: The combination of enobosarm and pembrolizumab was well tolerated and showed a modest clinical benefit rate of 25% at 16 weeks. Future trials investigating androgen receptor‐targeted therapy in combination with immune checkpoint inhibitors are warranted. Background: Luminal androgen receptor is a distinct molecular subtype of triple‐negative breast cancer (TNBC) defined by overexpression of androgen receptor (AR). AR‐targeted therapy has shown modest activity in AR‐positive (AR+) TNBC. Enobosarm (GTx‐024) is a nonsteroidal selective androgen receptor modulator (SARM) that demonstrates preclinical and clinical activity in AR+ breast cancer. The current study was designed to explore the safety and efficacy of the combination of enobosarm and pembrolizumab in patients with AR+ metastatic TNBC (mTNBC). Methods: This study was an open‐label phase II study for AR+ (≥10%, 1+ by immunohistochemistry [IHC]) mTNBC. Eligible patients received pembrolizumab 200 mg intravenous (IV) every 3 weeks and enobosarm 18 mg oral daily. The primary objective was to evaluate the safety of enobosarm plus pembrolizumab and determine the response rate. Peripheral blood, tumor biopsies, and stool samples were collected for correlative analysis. Results: The trial was stopped early because of the withdrawal of GTx‐024 drug supply. Eighteen patients were enrolled, and 16 were evaluable for responses. Median age was 64 (range 36–81) years. The combination was well tolerated, with only a few grade 3 adverse events: one dry skin, one diarrhea, and one musculoskeletal ache. The responses were 1 of 16 (6%) complete response (CR), 1 of 16 (6%) partial response (PR), 2 of 16 (13%) stable disease (SD), and 12 of 16 (75%) progressive disease (PD). Response rate (RR) was 2 of 16 (13%). Clinical benefit rate (CBR) at 16 weeks was 4 of 16 (25%). Median follow‐up was 24.9 months (95% confidence interval [CI], 17.5–30.9). Progression‐free survival (PFS) was 2.6 months (95% CI, 1.9–3.1) and overall survival (OS) was 25.5 months (95% CI, 10.4–not reached [NR]). Conclusion: The combination of enobosarm and pembrolizumab was well tolerated, with a modest clinical benefit rate of 25% at 16 weeks in heavily pretreated AR+ TNBC without preselected programmed death ligand‐1 (PD‐L1). Future clinical trials combining AR‐targeted therapy with immune checkpoint inhibitor (ICI) for AR+ TNBC warrant investigation.